In vitro assessment of heavy metal resistance and probiotic characteristics of the exopolysaccharide-producing Lactiplantibacillus planatrum O7S1 isolated from fermented olives - Zeghad, Imen; Aliouche, Nadia; Ouled-Haddar, Houria; Roula, Hanane; Bouremmad, Farida; Sifour, Mohamed; Korkmaz, Kader; Dertli, Enes (SPRINGER, 2025)
Heavy metal pollution is a significant environmental and health issue linked to industrial progress. This study aims to characterize a Lactiplantibacillus plantarum O7S1, isolated from fermented olives, for its exopolysaccharide (EPS) production, resistance to chromium (VI), nickel (II), cadmium (II), lead (II), and zinc (II), and probiotic traits, with potential applications in detoxifying these pollutants in the digestive tract or in fermented foods. Identified via 16S rRNA gene sequencing, Lpb. plantarum O7S1 demonstrated EPS production and slime-biofilm formation in hypersucrose and Congo Red agar. The strain showed high tolerance to Cr (VI), Ni (II), Zn (II), and Pb (II), but not to Cd (II), with the highest minimum inhibitory concentrations of 1000 mg/L for Cr (VI), Pb (II), and Ni (II), 850 mg/L for Zn (II), and 80 mg/L for Cd (II). Heavy metal stress significantly increased EPS production, likely offering protection against metal toxicity. The strain also exhibited strong probiotic traits, including tolerance to phenol (97.16% and 86.07% at 0.2% and 0.5%, respectively), bile salts (72.27%), and low pH (72.6%), as well as a significant adhesion to epithelial cells. Its cell surface properties included 66.45% hydrophobicity and auto-aggregation rates of 30.16% and 67.43% after 4 and 24 h, respectively. Furthermore, the strain displayed a safe profile with no hemolytic activity and sensitivity to most tested antibiotics. This study suggests that Lpb. plantarum O7S1 is a promising and safe probiotic candidate for bioremediation of heavy metal toxicity in organisms or food products, especially for Ni, Pb, Cr, and Zn.
Keywords: Bioremediation; Heavy metals; Exopolysaccharides; Lactiplantibacillus plantarum; Probiotic; LACTIC-ACID BACTERIA; ADHESION PROPERTIES; LACTOBACILLUS; IDENTIFICATION; AGGREGATION; BIOSORPTION; CHICKEN; ABILITY; Life Sciences & Biomedicine - Other Topics